The Impact of Disclosure of Sustainability Reports on Corporate Financial Performance: An Applied Study on Private Banks in Erbil - Kardar Ismael Hamad; Amanj Younes Osman (Zanco Journal of Humanity Sciences)
Sustainability reporting has become an essential practice for corporations seeking to align their business strategies with environmental, social, and governance (ESG) principles. This applied study examines the impact of sustainability reporting disclosure on corporate financial performance by analyzing secondary data from three private banks operating in Erbil, Kurdistan Region of Iraq. The study adopts a quantitative research methodology, utilizing correlation and regression analyses to evaluate the relationship between ESG disclosure and key financial indicators return on assets (ROA), return on equity (ROE), and stock performance. Data were collected from annual reports, financial statements, and publicly available sustainability disclosures for the years 2020 to 2023. The sample includes three banks selected based on the availability and consistency of their ESG reporting during the specified period. The findings reveal a positive association between sustainability reporting and financial performance, suggesting that enhanced ESG practices contribute to greater investor confidence, improved market valuation, and effective risk management. Banks with higher sustainability scores demonstrate stronger profitability and lower financial volatility. These results underscore the strategic importance of sustainability integration in driving long-term corporate success.